The influence of palm oil fuel ash and metakaolin on the strength of concrete and crack resistance of reinforced concrete beam: a review - De’nan, Fatimah; Johari, Megat Azmi Megat; Nyandau, Shaneez Christie Anak; Hashim, Nor Salwani (Multi-Science Publishing, 2022)
Purpose The purpose of this study is to know the influence of palm oil fuel ash and metakaolin on the strength of concrete and crack resistance of reinforced concrete beam. An ordinary portland cement has been used in the concretes production where it is an important material to be considered due to its nature that reacts with every substance present. During the cement production, a significant amount of carbon dioxide is emitted from the clinker in rotary kiln and lot of energy is required in the production processes. Such an event can be prevented by replacing the part of cement with metakaolin (MK) and palm oil fuel ash (POFA). Aside from being a cementitious alternative, the materials can also contribute to a greener environment and more sustainable building, as POFA is available in Malaysia and may be used to substitute cement and minimize pollution.